2014
DOI: 10.1007/s00464-014-3915-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety of transvaginal hybrid NOTES cholecystectomy: a systematic review and meta-analysis

Abstract: TVC is safe when performed by appropriately trained surgeons and may be associated with a faster return to normal activities and decreased postoperative pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 25 publications
3
32
0
1
Order By: Relevance
“…Another clear benefit of TVC is improved cosmesis. Importantly, there appears to be no significant difference in postoperative complications or rate of bile duct injury between TVC and CLC in these trials, conducted in centers of excellence and on selected patients [50] . Moreover, several studies reported no dyspareunia or difference in return to sexual activity between TVC and CLC groups after shortterm follow up [4749] .…”
Section: Natural Orifice Transluminal Endoscopic Cholecystectomymentioning
confidence: 89%
See 2 more Smart Citations
“…Another clear benefit of TVC is improved cosmesis. Importantly, there appears to be no significant difference in postoperative complications or rate of bile duct injury between TVC and CLC in these trials, conducted in centers of excellence and on selected patients [50] . Moreover, several studies reported no dyspareunia or difference in return to sexual activity between TVC and CLC groups after shortterm follow up [4749] .…”
Section: Natural Orifice Transluminal Endoscopic Cholecystectomymentioning
confidence: 89%
“…This technique is associated with longer operative time than CLC, and the conversion rate of TVC to CLC is estimated at 10% [47] . To date, three randomized control trials have been published, comparing transvaginal hybrid cholecystectomy to conventional [47,48] or needlescopic [49] laparoscopic cholecystectomy, along with one metaanalysis [50] . The proponents of NOTES cite reduced postoperative pain as an advantage of TVC over CLC.…”
Section: Natural Orifice Transluminal Endoscopic Cholecystectomymentioning
confidence: 99%
See 1 more Smart Citation
“…It has not been reported in any of the larger gynecologic case series or more contemporary NOTES trials. 15,17,2022 Despite concerns regarding bacterial seeding of the abdominal cavity by opening a natural orifice, infection rates appear comparable to those of the transabdominal approach, and no strong evidence from bacteriological studies supports these fears. Impact on female sexual function is worthy of strong consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Hauptvorteil von NOTES in geringeren postoperativen Schmerzen, einer rascheren Erholung, weniger Wundkomplikationen und Narbenhernien [2,14,18,22].…”
Section: Implementierung Der Hybrid-notes-sigmoidektomie Bei Divertikunclassified